2014
DOI: 10.1111/cbdd.12280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Novel Diarylpentanoid Analogues of Curcumin on Secretory Phospholipase A2, Cyclooxygenases, Lipo‐oxygenase, and Microsomal Prostaglandin E Synthase‐1

Abstract: Arachidonic acid and its metabolites have generated a heightened interest due to their significant role in inflammation. Inhibiting the enzymes involved in arachidonic acid metabolism has been considered as the synergistic anti-inflammatory effect. A series of novel curcumin diarylpentanoid analogues were synthesized and evaluated for their inhibitory effects on activity of secretory phospholipase A2 , cyclooxygenases, soybean lipo-oxygenase as well as microsomal prostaglandin E synthase-1. Among the curcumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 37 publications
0
20
0
2
Order By: Relevance
“…13,14 It is also noted from literature that the inhibition of more than one enzyme involved in different pathways of arachidonic acid metabolism lead to a synergistic anti-inflammatory effect with enhanced spectrum of activity. [15][16][17] The virtual combinatorial library is generated routinely for small molecules during the drug discovery cycle and screened based on their predicted physicochemical properties, activities, specificities, etc. [18][19][20] The virtual screening is useful in selecting a smaller set of promising hits from a large set of compound libraries.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 It is also noted from literature that the inhibition of more than one enzyme involved in different pathways of arachidonic acid metabolism lead to a synergistic anti-inflammatory effect with enhanced spectrum of activity. [15][16][17] The virtual combinatorial library is generated routinely for small molecules during the drug discovery cycle and screened based on their predicted physicochemical properties, activities, specificities, etc. [18][19][20] The virtual screening is useful in selecting a smaller set of promising hits from a large set of compound libraries.…”
Section: Introductionmentioning
confidence: 99%
“…Diarylpentanoids have been shown to exhibit remarkable antiinflammatory activity based on their positive inhibitions on a wide range of pro-inflammatory cytokines, enzymes and mediators such as nitric oxide (NO), prostaglandins (PGs), tumor necrosis factor alpha [TNF-α, interleukins, lipoxygenase (LOX) and cyclooxygenases]. [15][16][17][18] They are also found to display great anti-cancer properties as they significantly inhibited the growth of various cancer cell lines including breast, lung, colon, pancreas and prostate cancer cells, through their anti-proliferative and anti-angiogenic activities. [19][20][21][22][23] Unlike curcumin, diarylpentanoids are chemically stable at physiological pH and metabolically stable in rat liver microsomes, which make them the most impactful candidates among curcuminoids deserving further intensive investigations towards developing novel bioactive molecules with good stability and bioavailability Previously, we have shown that α,β-unsaturated β-diketone and cyclohexanone fragments are crucial for diarylpentanoids' bioactivities in different studies.…”
mentioning
confidence: 99%
“…Syntheses of the compounds 1a, 1b, 1c, 1d, 1e, 1f, 2a, 2b, 2c, 2d, 2e, 2f, 3a, 3b, 3c, 3d and 3f were reported previously (Ahmad et al, 2014;Hosoya et al, 2012;Jantan et al, 2012;Liang et al, 2009;Zhao et al, 2010). The diarylpentanoid analogues of curcumin were evaluated for their inhibitory effects on PMN chemotaxis, intracellular and extracellular ROS production and suppression effect on PMN phagocytosis.…”
Section: General Methodsmentioning
confidence: 99%
“…Synthetic curcumin analogues can be obtained by the classic base-/acid-catalysed Claisen Schmidt condensation reaction between the respective ketones and aromatic aldehydes (Ahmad et al, 2014;Rajput and Kaur, 2012). Though academic work relating to biological activities of curcumin has been published as early as 1949 (Schraufstatter and Bernt, 1949), insufficient studies on this interesting compound coupled by its poor bioavailability (Anand et al, 2007) have hindered the progress for curcumin to be developed adequately as a drug entity.…”
Section: Introductionmentioning
confidence: 99%